PROFESIONAL GURU SOSIOLOGI DI SMA NEGERI 7 PADANG KECAMATAN KOTO TANGAH KOTA PADANG - Satoutou, Martinus Liliu (Pendidikan Sosiologi, 2014)
The problem in this study is how the Teachers Professional Competence Sociology at SMA 7 Padang. The purpose of this study was to describe Teacher Professional Competency subjects Sociology at SMA 7 Padang. This study uses qualitative and descriptive research type. Purposive sampling informant selection techniques and methods of data collection are observation, documentation and interviews with Lexy Moleong data analysis are: data collection, data reduction, data presentation and draw conclusions. Based on the results of research on Teacher Professional Sociology at SMA 7 Tangah Koto Padang Subdistrict, for control of the structure, the concept, and thought patterns that support scientific subjects of teaching, teachers participated in the discussion MGMPs, reading and training. To master the competency standards and competency of teaching basic subjects teachers participated in the workshop. To develop learning materials of teaching creatively, teacher seminars and discussions. In order to develop the basis of sustainable professionalism with reflective action, continuing education teachers kejenjang higher with college back in college and make scientific papers Classroom Action Research (CAR), and to take advantage of information and communications technology for self-development teacher training or upgrading.